The Strengthening of the Institutional Corrections For Effective Rehabilitation in Kenya - Birech, Jeniffer Kosgey (Advances in Social Sciences Research Journal, 2020)
Strengthening the Institutional Corrections for Effective Rehabilitation in Kenya Jeniffer Birech Department of Sociology and Social Work Abstract Globally, Institutional Corrections continue to play a critical role in the rehabilitation of the offenders. It is estimated that there are more than 10.2 million offenders in prison including sentenced and pretrial prisoners. Statistics also show that 144 out of every 100,000 people are in prison. Similarly, in the last fifteen years the estimated world prison has increased by 25-35% hence the need to strengthen institutional corrections for better rehabilitation. In Kenya, the total prison population is about 53,841. This includes the pretrial detainees and remand prisoners. Additionally, there are 92 institutional corrections in Kenya. However, the prison system struggles with overcrowding, poor governance, insufficient coordination with other criminal justice systems and inadequate resources. As a result, the institutions have become breeding grounds for recidivism. This paper examines the development of the prison system, the evolution of the challenges and abuse of human rights. It will also examine how institutions can be strengthened. The paper recommends the need for more research to unearth more innovative ways of dealing with the challenges. There is need for inbuilt mechanisms to ensure good governance and accountability, re-integration and allocation of resources. In essence, a multisectoral approach need to be adopted for sustainable solutions. Key Words; Strengthening, Institutional Corrections, Rehabilitation, Prison, Kenya.